DETERMINAN RETURN SAHAM PADA PERUSAHAAN PERBANKAN DI INDONESIA : Untuk Mahasiswa UPN Veteran Jakarta - Kesia Natalia Manurung (2020)
This research is a quantitative study that aims to determine the stock returns of conventional banking companies listed on the Indonesia Stock Exchange (IDX). The financial ratios studied are liquidity ratios, leverage ratios, and profitability ratios. The dependent variable in this study is stock returns and independent variables, namely liquidity, leverage, and profitability. The population in this study were all conventional banking companies in Indonesia, amounting to 40 companies. The sample selection in this study was carried out using the Probability Sampling technique, with the number of samples to be taken determined using the Slovin formula. The type of data in this study is secondary data and the analysis model in this study is the regression and panel with the E-views program. The sample used in this study amounted to 36 conventional banking companies in the 2017-2019 period. The results of the panel data analysis evaluation use a significant level of 0.05 measuring liquidity has a negative effect on stock returns, leverage has no effect on stock returns, and profitability has a negative effect on stock returns.